2010
DOI: 10.5424/fs/2010193-9104
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Spanish black pine postdispersal seed predation in Central-eastern Spain

Abstract: In this research work, we specifically address post-dispersal Spanish black pine (Pinus nigra Arn. ssp salzmannii) seed predation at two different locations, one being the most common and representative location for the species and the other located on areas at their ecological limit of distribution in Cuenca Mountain (Spain). A modelling approach was employed to analyze the effect of stand and site characteristics and climate variables on the post-dispersal predation process. Each predator group (ants, rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
14
0
3
Order By: Relevance
“…Our results showed that predation reduced the Pinus pinaster below-ground seed bank, corroborating what had previously been reported for other Pine species in the Mediterranean basin (Castro et al 1999;Ordóñez and Retana 2004;Zong et al 2010;Lucas-Borja et al 2010). Predation was low during the seed rain period, when temperatures were higher, and increased during autumn, as Manso et al (2014) observed for Pinus pinea in the same study area (Northern Castilian plateau).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that predation reduced the Pinus pinaster below-ground seed bank, corroborating what had previously been reported for other Pine species in the Mediterranean basin (Castro et al 1999;Ordóñez and Retana 2004;Zong et al 2010;Lucas-Borja et al 2010). Predation was low during the seed rain period, when temperatures were higher, and increased during autumn, as Manso et al (2014) observed for Pinus pinea in the same study area (Northern Castilian plateau).…”
Section: Discussionsupporting
confidence: 91%
“…Hulme (1997) found that rodents avoided open areas whereas ants preferred them. Lucas-Borja et al (2010) did not find basal area of the stand to be significant, perhaps because only three density levels were considered in that study (low: 15-20 m2/ha; medium: 25-30 m2/ha; high: 35-40 m2/ha).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Several authors have cited a number of big problems for successful natural regeneration of Spanish black pine: irregular masting conditions, dry summers over a period of at least 3 years, excessive grazing and uncontrolled ploughing Lucas-Borja et al 2010Tíscar and Linares 2014). Moreover, forecasts suggest these pine forests will be soon one of the forest ecosystems hit hard by climate change, and their current distribution could shrink dramatically ).…”
Section: Introductionmentioning
confidence: 99%
“…o frondosas (Quercus ilex, Q. faginea, etc.). En los extremos (tanto inferior como superior) del gradiente altitudinal, P. nigra aparece como poblaciones relictas o aisladas que están fragmentadas en pequeñas masas (Lucas-Borja et al 2010a, 2010b. En las poblaciones de P. nigra estudiadas los suelos son calcáreos y generalmente poco profundos (Soil Survey Staff 1999), abarcando desde leptosoles rendzínicos a xerorthent típicos (LucasBorja et al 2011).…”
Section: Materials Y Métodos Especies Y Zonas De Estudiounclassified